Inhibition of miR-22-3p reduces kidney disease associated with systemic lupus erythematosus - Michell, Danielle L; Faust, Ashley; Moore, Jared L; Appleton, Brenna D; Ormseth, Michelle; Ramirez-Solano, Marisol; Sheng, Quanhu; Solus, Joseph F; Stein, C Michael; Vickers, Kasey C; Major, Amy S (bioRxiv, 2019)
Cellular microRNAs (miRNA) have proven to be critical regulators of inflammatory gene expression across many pathways within autoimmunity. Circulating miRNAs serve as a new class of disease biomarkers. Nevertheless, the functional roles of miRNAs, particularly extracellular miRNAs, in systemic lupus erythematosus (SLE) remain poorly understood. Therefore, we aimed to link changes in extracellular miRNAs to lymphocyte gene regulation and the pathophysiology of SLE. Here, we demonstrate that circulating miR-22-3p levels are associated with SLE, and miR-22-3p regulates T and B cell function and SLE-associated kidney disease. Based on high-throughput small RNA sequencing and real-time PCR, extracellular miR-22-3p levels were found to be significantly increased in whole plasma in human SLE subjects. To determine the functional impact of miR-22-3p in SLE, miR-22-3p loss-of-function studies were performed in a mouse model of SLE (B6.SLE1.2.3). We found that in vivo administration of locked-nucleic acid inhibitors of miR-22-3p (LNA-22) reduced lymphocyte accumulation in both the spleen and lymph nodes compared to LNA scramble (LNA-Scr) control-treated mice. Strikingly, LNA-22-3p treatments reduced kidney disease pathology and glomerular IgG deposition compared to LNA-Scr treatments in SLE mice. Moreover, miR-22-3p inhibition reduced the proportion of T effector memory IFN-g producing CD4+ T cells, suggesting that miR-22-3p regulates Th1 T cell differentiation. We also found that miR-22 inhibition in mice reduced STAT1 phosphorylation in the kidney which was correlated with loss of IFN-g production by splenic CD4+ T cells. In conclusion, our findings suggest that miR-22-3p is a critical regulator of SLE-associated CD4+ T cell immunity and kidney disease. These results provide therapeutic potential for limiting splenic Th1 signaling and preventing the progression of lupus nephritis.